2006
DOI: 10.2146/ajhp050519
|View full text |Cite
|
Sign up to set email alerts
|

Risks versus benefits of cyclooxygenase-2-selective nonsteroidal antiinflammatory drugs

Abstract: PURPOSE: A summary of the basic science underlying the current controversies regarding cyclooxygenase-2 (COX-2)-selective nonsteroidal antiinflammatory drugs (NSAIDs), including data on their cardiovascular safety, their gastrointestinal (GI) benefits, cost-effectiveness, physician-prescribing trends, and recommendations for prescribing these agents is presented. SUMMARY: A number of randomized controlled trials (RCTs) have reported that COX-2-selective NSAIDs increase cardiovascular events, although there app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
37
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 89 publications
1
37
0
3
Order By: Relevance
“…Taking into account the high cost of COX-2 selective inhibitors (17,18), such as valdecoxib, in comparison with the conventional NSAIDS like piroxicam, our data support the suggestion that there are no sufficient clinical advantages for the prescription of valdecoxib after lower third molar removal.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Taking into account the high cost of COX-2 selective inhibitors (17,18), such as valdecoxib, in comparison with the conventional NSAIDS like piroxicam, our data support the suggestion that there are no sufficient clinical advantages for the prescription of valdecoxib after lower third molar removal.…”
Section: Discussionsupporting
confidence: 77%
“…It is worth mentioning that recent reports have suggested an increased risk of cardiovascular events for patients taking coxibs. Therefore, clinicians must consider the efficacy, gastrointestinal and cardiovascular risks, concomitant medications and costs when determining the appropriateness of COX-2 selective NSAID therapy (14)(15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, both selective and non-selective COX inhibitors can impair renal flow and glomerular filtration, as well as sodium and potassium excretion, which leads to swelling, pressure increase and hyperkalemia. This was confirmed by numerous studies [16,18]. Moreover, it was demonstrated that selective COX-2 inhibitors inhibit renin secretion in the macula densa, stimulated by a decrease in sodium concentration.…”
Section: Organ Toxicitymentioning
confidence: 52%
“…This situation comes about depending on the inhibition of platelet activity by COX-1. Selective COX-2 inhibitors do not display antithrombotic action, but can intensify blood coagulation by inhibiting the synthesis of prostacyclins in the endothelium [18,27]. This, however, was not explicitly confirmed in clinical trials [23].…”
Section: Organ Toxicitymentioning
confidence: 99%